Moddalarning elektr o’tkazuvchanligi haqida ayrim muhim tushunchalar - Ismoilova Iroda Erkinovna (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article presents the types of substances according to their electrical conductivity and the classification of each type. The properties of electrical conduction in metals, dielectrics and semiconductors are described.